New insights on mcr-1-harboring plasmids from human clinical Escherichia coli isolates - Martino, Florencia (2024)
Mobile colistin resistance (mcr) genes were described recently in Gram-negative bacteriaincluding carbapenem-resistant Enterobacterales. There are ten mcr genes described in differentGram-negative bacteria, however, Escherichia coli harboring mcr-1 gene is by far themost frequent combination. In Argentina, mcr-1 gene was characterized only on plasmidsbelonging to IncI2 group. The aim of this work was to get new insights of mcr-1-harboringplasmids from E. coli. Eight E. coli isolates from a larger collection of 192 clinical E. coli isolatescarrying the mcr-1 gene were sequenced using next generation technologies. Threeisolates belonged to ST131 high-risk clone, and five to single ST, ST38, ST46, ST226,ST224, and ST405. Eight diverse mcr-1-harboring plasmids were analyzed: IncI2 (1), IncX4(3), IncHI2/2A (3) and a hybrid IncFIA/HI1A/HI1B (1) plasmid. Plasmids belonging to theIncI2 (n = 1) and IncX4 (n = 3) groups showed high similarity with previously described plasmids.Two IncHI2/HI2A plasmids, showed high identity between them, while the third,showed several differences including additional resistance genes like tet(A) and floR. OneIncFIA/H1A/H1B hybrid plasmid was characterized, highly similar to pSRC27-H, a prototypeplasmid lacking mcr genes. mcr-1.5 variant was found in four plasmids with three differentInc groups: IncI2, IncHI2/HI2A and the hybrid FIA/HI1A/HI1B plasmid. mcr-1.5 variant isalmost exclusively described in our country and with a high frequency. In addition, six E. coliisolates carried three allelic variants codifying for CTX-M-type extended-spectrum-β-lactamases:blaCTX-M-2 (3), blaCTX-M-65 (2), and blaCTX-M-14 (1). It is the first description of mcr-1harboring plasmids different to IncI2 group in our country. These results represents newinsights about mcr-1 harboring plasmids recovered from E. coli human samples from Argentina,showing different plasmid backbones and resistance gene combinations.